2007
DOI: 10.1016/j.jneumeth.2007.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for gene expression profiling of human brain

Abstract: Gene expression profiles of postmortem brain tissue represent important resources for understanding neuropsychiatric illnesses. The impact(s) of quality covariables on the analysis and results of gene expression studies are important questions. This paper addressed critical variables which might affect gene expression in two brain regions. Four broad groups of quality indicators in gene expression profiling studies (clinical, tissue, RNA, and microarray quality) were identified. These quality control indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 82 publications
4
96
2
Order By: Relevance
“…As to agonal state, gene expression profiles in the post mortem brain are influenced by asphyxia/ ischemia during agony (e.g. Atz et al, 2007;Ervin et al, 2007;Vawter et al, 2006). Recently, Li et al (2004) found that individuals who suffered prolonged agonal states exhibited a consistent change in expression of various genes, whereas those who experienced brief deaths caused by accidents, acute cardio-respiratory events or asphyxia, generally did not (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to agonal state, gene expression profiles in the post mortem brain are influenced by asphyxia/ ischemia during agony (e.g. Atz et al, 2007;Ervin et al, 2007;Vawter et al, 2006). Recently, Li et al (2004) found that individuals who suffered prolonged agonal states exhibited a consistent change in expression of various genes, whereas those who experienced brief deaths caused by accidents, acute cardio-respiratory events or asphyxia, generally did not (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since post-mortem delay can significantly alter gene expression profiles (Atz et al, 2007;Ervin et al, 2007;Vawter et al, 2006), subjects with a post-mortem delay longer than 12 h were also excluded from the present account. Brains from suicide victims with MDD (5 males and 3 females) and from controls (8 males and 8 females) were studied.…”
Section: Methodsmentioning
confidence: 99%
“…One method is to develop animal and cellular models that have profiles similar to BPD and SZ gene expression profiles and to show that the pathophysiology involves mitochondrial-related gene expression. The other method is to perform rigorously controlled studies of covariates and gene expression (62,69,(79)(80)(81) which we further comment upon below.…”
Section: Altered Mitochondrial Gene Expression In Psychiatric Disordersmentioning
confidence: 99%
“…This ANCOVA was restricted to subjects above the median pH of 6.57 and with the covariates of pH and age. Although covariate analysis approach might be useful with the strong effect of pH, it may not be linear through the lower pH range, when subjects may show a ceiling or floor effect depending on the direction of association (7)(8)(9)(16)(17)(18)(19). Therefore, we attempted to use subjects with above-median pH as an indicator of fewer residual agonal effects.…”
Section: Restricted Analysis Of Subjects By Ancovamentioning
confidence: 99%